Effects of Iron Deficiency Anemia and its Treatment on Ghrelins, Obestatin and Heat Shock Protein 70 - Kasar, Taner; Akarsu, Saadet; Aydin, Süleyman (International Journal of Child Health and Nutrition, 2023)
The impact of iron deficiency anemia (IDA) and its treatment on increased levels of heat shock protein 70 (HSP70) in settings with higher tissue stress induced by both ghrelin, which is both an antioxidant and a food intake stimulant, and also obestatin with opposing effects were investigated. The association of pica with these parameters was also examined. The study included 28 patients with IDA and 28 healthy controls. While acyl ve des-acyl ghrelin values were lower (p<0.05) in IDA. With treatment, ghrelin levels climbed. In IDA, obestatin levels were higher than the control values (p<0.05). With the IDA treatment, acyl and des-acyl Ghrelin levels increased. Contrarily, obestatin values fell down. The concentration of HSP 70 in IDA and during its therapy was above control values. Acyl, des-acyl ghrelin, obestatin, and HSP70 levels were increased in the pica group. In the pica group obestatin/acyl ghrelin ratio was comparatively higher (p<0.05). In IDA decrease in ghrelin and an increase in obestatin levels are observed, while HSP 70 remains the same. An increase in the obestatin/acyl ghrelin ratio might be responsible for the pica disorder.